Proteomic Analysis and Functional Validation of a Brassica oleracea Endochitinase Involved in Resistance to Xanthomonas campestris - Santos, Cristiane; Nogueira, Fábio C. S.; Domont, Gilberto B.; Fontes, Wagner; Prado, Guilherme S.; Habibi, Peyman; Santos, Vanessa O.; Oliveira-Neto, Osmundo B.; Grossi-de-Sá, Maria Fatima; Jorrín-Novo, Jesus V.; Franco, Octavio L.; Mehta, Angela (Frontiers in Plant Science, 2019)
Black rot is a severe disease caused by the bacterium Xanthomonas campestris pv. campestris (Xcc), which can lead to substantial losses in cruciferous vegetable production worldwide. Although the use of resistant cultivars is the main strategy to control this disease, there are limited sources of resistance. In this study, we used the LC-MS/MS technique to analyze young cabbage leaves and chloroplast-enriched samples at 24 h after infection by Xcc, using both susceptible (Veloce) and resistant (Astrus) cultivars. A comparison between susceptible Xcc-inoculated plants and the control condition, as well as between resistant Xcc-inoculated plants with the control was performed and more than 300 differentially abundant proteins were identified in each comparison. The chloroplast enriched samples contributed with the identification of 600 additional protein species in the resistant interaction and 900 in the susceptible one, which were not detected in total leaf sample. We further determined the expression levels for 30 genes encoding the identified differential proteins by qRT-PCR. CHI-B4 like gene, encoding an endochitinase showing a high increased abundance in resistant Xcc-inoculated leaves, was selected for functional validation by overexpression in Arabidopsis thaliana. Compared to the wild type (Col-0), transgenic plants were highly resistant to Xcc indicating that CHI-B4 like gene could be an interesting candidate to be used in genetic breeding programs aiming at black rot resistance.